Community participation as a human right: Perspective of Indonesia's nickel downstream on the natural resource curse phenomenon - Daryanti Daryanti; Albertus Sentot Sudarwanto; Bayu Sujadmiko (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: Various controversies over Indonesia's nickel downstreaming policy as a government move to add economic value to mining products are important issues that need to be studied. This problem is mainly because Indonesia is a developing country that has abundant natural resources, but has not been able to improve welfare and development for communities in mining areas, especially in the aspect of community participation. This research then highlights the perspective of the Natural Resource Curse (NRC) phenomenon for Third World Approaches to International Law (TWAIL) countries in the paradox of development stemming from the exploitation of natural resources. Purpose/Study Objectives: Community involvement in mining and other industrial activities is needed. This is related to decision making. For example, in Environmental Impact Assessment/ Analisis Mengenai Dampak Lingkungan (AMDAL) and other activities related to the lives and livelihoods of communities around mining activities. The basis of public participation is part of human rights as stated in the Constitution and International Conventions that have been ratified by Indonesia. Design/Methodology/Approach: This research uses legal normative research by examining legislation regarding nickel downstreaming as stated in Law No. 30 of 2020 on the Second Amendment to Law No. 4 of 2009 On Mineral and Coal Mining and Law No 6 of 2023 on Cipta Kerja, Findings: The findings in this study show the lack of community involvement in mining and other industrial activities in Indonesia. The existence of community participation as a human right is necessary to achieve a balance of economic growth and environmental protection as an anti-thesis to the curse of natural resources. In addition, governance and enforcement and supervision by the government in the mining sector need to be carried out effectively. Paper Type: Research Article